Bimetal Adsorption by Cottonseed Carbon: Equlibrium and Kinetic Studies - K. Srinivasan; E. Sathiya (E-Journal of Chemistry)
The simultaneous adsorption of Pb(II) and Hg(II) on cottonseed carbon (CSC) was employed for the removal of these metals from wastewater. The influence of various factors such as agitation time, pH and carbon dosage on the adsorption capacity has been studied. Langmuir and Freundlich equation could be used to interpret adsorption data. Sorption kinetics has indicated that reversible first order kinetics model could be applied with film diffusion as the controlling mechanism.